Quality Control Related to Inventory Loss of Animal Feed Raw Materials using I-MR Control Map (Case Study: PT Cargill Indonesia, Plant Semarang) - Amanda Sofiana; Eva Pramudea Safitri (OPSI, 2023)
Quality control is one of the things that needs to be considered by the company to maintain the product quality from the process until the product reaches the customers. PT. Cargill Indonesia Semarang Plant is a subsidiary under the Cargill company which is a global company serving the food, agriculture, finance and industrial sectors. The company has an external warehouse that stores both local and imported raw materials. The raw material undergoes loading and unloading process and weighing at the plant as well as 3 Metric Ton (MT) scales. However, there are differences in the two scales due to shrinkage with different factors. Therefore, it is necessary to carry out quality control on inventory loss of raw materials by using the I-MR control chart to find out the amount of losses that occur in each raw material statistically and analyze with fishbone diagram and Root Cause Analysis (RCA) to find out the root causes of losses and improve its quality control in the unloading process of raw materials.